2020
DOI: 10.1101/2020.03.26.20043042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis and Prediction of COVID-19 Patients’ False Negative Results for SARS-CoV-2 Detection with Pharyngeal Swab Specimen: A Retrospective Study

Abstract: Background: False negative results of SARS-CoV-2 nucleic acid detection pose threats to COVID-19 patients and medical workers alike.Objective: To develop multivariate models to determine clinical characteristics that contribute to false negative results of SARS-CoV-2 nucleic acid detection, and use them to predict false negative results as well as time windows for testing positive. Design: Retrospective Cohort Study (Ethics number of Tongji Hospital Patients: 1,324 outpatients with COVID-19Measurements: Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…A total of 43 studies including 10,676 COVID-19 patients (confirmed by laboratory real-time reverse transcription polymerase chain reaction [RT-PCR] testing) were included in the overall analysis. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,41,42,45,47,[49][50][51][52][53][54][55]58,59,[62][63][64][65][66][67][68][69][70][71]73,76 The pooled prevalence of diarrhea symptoms across these studies was 7.7% (95% CI, 7.2%-8.2%). When analyzing by country (studies from China vs studies from other countries), the pooled prevalence of diarrhea in studies from countries other than China was much higher at 18.3% (95% CI, 16.6%-20.1%).…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43 studies including 10,676 COVID-19 patients (confirmed by laboratory real-time reverse transcription polymerase chain reaction [RT-PCR] testing) were included in the overall analysis. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,41,42,45,47,[49][50][51][52][53][54][55]58,59,[62][63][64][65][66][67][68][69][70][71]73,76 The pooled prevalence of diarrhea symptoms across these studies was 7.7% (95% CI, 7.2%-8.2%). When analyzing by country (studies from China vs studies from other countries), the pooled prevalence of diarrhea in studies from countries other than China was much higher at 18.3% (95% CI, 16.6%-20.1%).…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
“…[20][21][22][23][25][26][27][28]30,[33][34][35]38,41,42,[44][45][46][49][50][51][52][53][54][55]60,[62][63][64][65][66][67][68][70][71][72][73][74]76 In 3 studies including 1701 outpatients, the pooled prevalence was 4.0% (95% CI, 3.1%-5.1%). 31,59,63 As part of the sensitivity analysis, we identified 35 studies including 9717 patients that described diarrhea, and explicitly reported that it was one of the initial presenting sympto ms. [20][21][22][23][26][27][28]31,…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
“…The diagnosis of COVID-19 is confirmed by a positive reverse transcriptase polymerase chain reaction (RT-PCR) from nose, throat, sputum or bronchoalveolar lavage. The sensitivity of this test is suboptimal (50-80%), probably due to sampling error, low viral loads as well as timing of the sample in the disease course (3,4). In most COVID-19 patients, non-contrast chest CTscanning shows bilateral ground glass opacities with a peripheral and basal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…CT: computed tomography the gold standard for the diagnosis of COVID-19, false negative test results are not too low because of many factors such as test kit, sampling tube, specimen sampling, drugs administered to patients etc. (5). Chest CT is of great value in the diagnosis of COVID-19 because of its simplicity and ease, especially in patients with or without clinical symptoms (3,6,7).…”
mentioning
confidence: 99%